Two Patients with Atypical Choroidal Detachment - Joseph W. Fong (Case Reports in Ophthalmology, 2021)
Serous choroidal detachment that is caused by rhegmatogenous retinal detachment (RRD) may present a significant diagnostic challenge as delayed recognition and repair of the underlying RRD can severely impact the final anatomical and visual outcome. We report 2 consecutive patients with atypical choroidal detachments who were later found to have underlying RRDs. A 71-year-old female presented with a 1-week history of painful vision loss and floaters in the left eye. Examination revealed choroidal detachments in the nasal and temporal periphery and an overlying retinal detachment with shifting subretinal fluid. However, no retinal breaks were identified. An extensive laboratory workup and imaging of the orbits were unrevealing. She was treated with 80 mg oral prednisone daily for 2 weeks with subsequent resolution of the choroidals but persistence of the retinal detachment. Similarly, a 52-year-old male presented with a 3-week history of flashes and floaters followed by painful vision loss in the left eye 1 day prior to presentation. He had hand motion vision OS and the intraocular pressure was undetectable by hand-held tonometry OS. Dense brunescent cataract prevented adequate viewing of the posterior pole. B-scan ultrasonography revealed a funnel retinal detachment, with homogenous choroidal echogenicities suggestive of hemorrhagic choroidal detachment. Extensive laboratory workup was unrevealing. The patient was started on 60 mg oral prednisone and re-evaluated every 2 days, but ultrasonography revealed persistence of the choroidal detachment after 1 week. The diagnosis of RRD with an associated choroidal detachment should be considered, even in the absence of an identifiable causative retinal break.